Socialization and Assistance in Strengthening Food Security through Food Security Strategy Seminar Activities in Jambenenggang Village (Group 8 Food Security Division) - Yepi Sopian; Dita Julianti; Septiani Nalurita; Sheli Selwina; Siti Masamah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Adequate food security does not guarantee the possibility of change in the future, so anticipatory measures are taken to ensure continuity of food availability. This article aims to describe socialization and assistance in strengthening food security through food security strategy seminars to increase economic independence and competitiveness in Jambenenggang village, Kebonpedes sub-district. This seminar method is carried out through various stages, including coordination, seminar implementation and evaluation. The conclusion is that, 1) Coordinating activities for the preparation of this seminar went smoothly, for speakers for this seminar, Mr. Ahmad Zenal Muttaqin then also invited the chairman of IWAPI (Indonesian Entrepreneurs Women's Association) Kebonpedes sub-district, Kebonpedes sub-district head and Jambenenggang village head. 2) Implementation of a seminar for the people of Jambenenggang village about food security has an impact on understanding the importance of food security to be able to think and act productively in order to have a competitive economy